Режимы работы системы тягового электроснабжения переменного тока с устройствами компенсации реактивной мощности - Доманский, И.В. (Електротехніка і електромеханіка, 2015)
В статье дана сравнительная оценка регулируемых установок компенсации реактивной мощности и разработана
методика выбора их параметров и мест размещения в электротяговой сети. Проведены исследование и анализ режимов работы электротяговых сетей и питающих линий энергосистем. Выделены факторы, которые в наибольшей
степени влияют на энергосбережение. В статті проведена порівняльна оцінка регульованих установок компенсації реактивної потужності та розроблена
методика вибору їх параметрів і місць розміщення в електротяговій мережі. Проведені дослідження та аналіз режимів роботи електротягових мереж і ліній енергосистем, що їх живлять. Виділені фактори, які в найбільшій мірі
впливають на енергозбереження. The paper presents a systematic analysis of existing methods of
reactive power compensation. The study of operating modes of the
systems external and traction power supply is carried out. The
methodology for selecting promising compensation schemes and
energy-saving in the traction networks AC electrified railway lines
is offered. The comparative evaluation of prospective controlled
compensation devices shows that use of seamlessly adjustable
devices with unregulated condensing the battery and with parallel
translator regulated with thyristor unit and with filters to reduce
harmonics bond to the large capital investments. For traction
networks of domestic railways payback period is more than 10-15
years. The most promising for traction power supply today is a
stepwise adjustable devices of reactive power compensation. For
the efficient allocation of investments in programs and projects of
modernization of system traction power supply developed by the
methodology of selecting parameters and places placement devices transverse compensation in the system traction power supply, which is based on the use of software systems with imitation
of interconnected instant circuits moving loads of electric rolling
stock. Based on the results of multiple calculations full factor
experiment when simulating work of the systems traction power
supply during the day marked the most influencing factors on
energy-saving in process freight on electric traction and established the extent of their influence. These include the overflows of
power, the resistance of traction network, reactive power compensation, power supply circuits and the organization of trains. Innovative technologies energy-saving railways from positions of consideration their close connection with the systems external power
supply are proposed.